Microbiological quality of raw sausage commercialized in the Great Metropolitan Area of Costa Rica - Redondo-Solano, Mauricio; Cordero-Calderón, Valery; Araya-Morice, Adriana (Agronomía Mesoamericana, 2022)
Introduction. In Latin America, reports on the microbiological quality of raw chorizo, or raw pork sausage, are limited, however, it is a widely consumed and traditional product. Objective. To determine the microbiological stability of the raw sausage in the Great Metropolitan Area (GAM) of Costa Rica. Materials and methods. Between January and August 2019, microbial shelf-life counts, and contamination indicators were carried out, as well as the detection of three pathogens (Salmonella spp., Listeria monocytogenes, and Clostridium perfringens) in fifty samples of raw chorizo obtained from butcher shops in the Great Metropolitan Area of Costa Rica. Results. Of the fifty samples analyzed, only one was found to be consumable according to the general parameters of bacterial count (total aerobic count [TAM], fungi and yeasts [HYL], and lactic acid bacteria [BAL]). The main cause of spoilage included a combination of BAL and HYL. In addition, the total coliform counts ranged between 105 and 106 UFC/g. From a safety standpoint, Salmonella spp. was isolated in 16 % of the samples, Listeria monocytogenes in 10 % and Clostridium perfringens was found in a single sample with a count of 5.00x101 CFU/g. Conclusion. Non-heat treated products, such as raw chorizo sold in the GAM of Costa Rica, are products that are highly susceptible to spoilage, which present high levels of contamination and that could behave as a vehicle for pathogens; therefore, it is recommended to improve manufacturing practices to prolong shelf life and guarantee consumer safety.